THE EFFECT OF ORGANIZATIONAL CONFLICT AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE AT PUBLIC ELEMENTARY SCHOOL NO. 035, TALANG UBI SUBDISTRICT, PALI REGENCY - Sukirman Sukirman; Fitri Oviyanti; Rohmadi Rohmadi; Zainal Berlian (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the effect of organizational conflict and organizational culture on teacher performance at SD Negeri No. 035 Talang Ubi District, PALI Regency, both partially and simultaneously, as well as to identify the most dominant variable. This study employs a quantitative approach with a verificative research design. The population consists of all 32 teachers, and the sampling technique used is total sampling. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The results show that partially, organizational conflict has a significant effect on teacher performance with a significance value of 0.013, and organizational culture also has a significant effect with a significance value of 0.043. Simultaneously, organizational conflict and organizational culture have a significant effect on teacher performance with a significance value of 0.002. The coefficient of determination (R²) of 0.358 indicates that 35.8% of teacher performance is influenced by these two variables, while the remaining percentage is influenced by other factors outside this study. Organizational conflict is the most dominant variable affecting teacher performance. Based on the findings, it can be concluded that effective management of organizational conflict and the strengthening of a positive organizational culture are essential in improving teacher performance. Therefore, schools are expected to create a conducive working environment through constructive conflict management and the development of an organizational culture that supports teacher professionalism.